Exercise as Therapy: Health and Well-Being - Archer, Trevor (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Physical exercise, in several guises, improves health and delivers a multitude of benefits for the aging brain and body, not least by delaying the aging process, but also by, its “scaffolding effect”, buttressing the physiological processes vulnerable to that level of credibility. The present account is based upon a systematic survey of published studies outlining the benefits of physical exercise an intervention to improve diverse health aspects, with the key-words “Physical exercise and Health” among all biomedical sources. Under conditions of neuropsychiatric and neurologic ill-health, child-adolescent maturation during healthy and illness developmental trajectories, neuroimmune and affective unbalance, and epigenetic pressures, exercise offers a large harvest of augmentations in health and well-being. Both animal models and human studies support the premise of manifest gains from regular exercise within several domains, besides cognitive function and mood, notably as the agency of a noninvasive, readily available therapeutic intervention.